Key Technologies and Standards of Autonomous Driving System Applied in Surface Mines - ZHANG Tao; LU Xiangyang; LI Lei; QIN Xiaohui; LUAN Xiaofei (Kongzhi Yu Xinxi Jishu)
The development and progress of autonomous driving technologies applied in surface mines was reviewed, the advantage resulted from the utilization of autonomous driving technologies in the mine operation was analyzed, the relevant standards were introduced, the key technologies of autonomous driving vehicles in surface mines were analyzed, and finally the domestic development of autonomous surface-mine systems was prospected.